The blue carbon wealth of nations - Christine Bertram; Martin Quaas; Thorsten B.H. Reusch; Athanasios T. Vafeidis; Claudia Wolff; Wilfried Rickels (Nature Climate Change, 2021)
Carbon sequestration and storage in mangroves, salt marshes and seagrass meadows is an essential coastal `blue carbon' ecosystem service for climate change mitigation. Here we offer a comprehensive, global and spatially explicit economic assessment of carbon sequestration and storage in three coastal ecosystem types at the global and national levels. We propose a new approach based on the country-specific social cost of carbon that allows us to calculate each country's contribution to, and redistribution of, global blue carbon wealth. Globally, coastal ecosystems contribute a mean ± s.e.m. of US190.670.167em±0.167em300.167embn0.167emyr-1 to blue carbon wealth. The three countries generating the largest positive net blue wealth contribution for other countries are Australia, Indonesia and Cuba, with Australia alone generating a positive net benefit of US22.80.167em±0.167em3.80.167embn0.167emyr-1 for the rest of the world through coastal ecosystem carbon sequestration and storage in its territory.
Keywords: 330; Climate-change mitigation; Economics; Marine biology